A Ratiometric Selective Fluorescent Probe Derived from Pyrene for Cu2+ Detection - Chunwei Yu; Mei Yang; Shuhua Cui; Yuxiang Ji; Jun Zhang (Chemosensors, 2022)
A novel ratiometric Cu2+-selective probe was rationally constructed based on pyrene derivative. Compared to other tested metal ions, the probe presented the selective recognition for Cu2+ which could be detected by a significant turn-on fluorescent response at 393 nm and 415 nm. Under the optimized conditions, a detection limit of 0.16 μM Cu2+ in aqueous media was found. Besides this, a 1:1 metal–ligand complex was confirmed by MS spectra and Job’s plot experiment, and the binding mode was also studied by 1H NMR experiment. Meanwhile, the fluorescence imaging in living cells was performed to detect Cu2+ with satisfactory results.